Circular Economic Analysis Of The Goroho Banana Processing Industry At Smes In Manado City Towards A Green Economy: A Case Study Of Kios Saraba Doa Ibu - Steefra D. Mangkay; Angel Helda Semuruk; Yuliana Mose; Ingrid Novelia Sembiring (UNIVED Press, 2025)
This research aims to analyze the application of the circular economy concept in the Goroho banana processing industry at the Micro, Small, and Medium enterprises (MSME) level, with a case study of Kios Saraba Doa Ibu in Manado City. This study uses a qualitative approach based on in-depth interviews and observations to identify resource and waste management practices and development potential to improve business sustainability. The analysis results show that Kios Saraba Doa Ibu still faces various challenges in implementing the circular economy, primarily in handling banana peel waste and using cooking oil management. However, there are significant opportunities for waste utilization and the Development of value-added products that can support the transition of this MSME towards more sustainable business practices. Strategic recommendations include improving the owner's knowledge capacity, investing in waste processing technology, and developing circular business models suitable for the local MSME context. This study is the first to integrate circular economy approaches with waste management in goroho banana processing at Manado City urban, generating an innovative analytical framework for sustainable MSME development.